Angiogenesis and Direct Myocardial Revascularization - Laham, Roger J.; Laham, Roger J.; Baim, Donald S.; Baim, Donald S. (Contemporary Cardiology, 2005)
Despite the rapid progress in surgical and catheter-based revascularization, an alternative treatment strategy is needed for the ever-increasing number of patients who are either not candidates for these therapies or remain symptomatic after revascularization and maximal ongoing medical treatment. In Angiogenesis and Direct Myocardial Revascularization, an interdisciplinary panel of pioneers and opinion leaders review the basic, preclinical, clinical, and developmental pathways to new treatment strategies, such as therapeutic angiogenesis and myogenesis. In their assessments, the authors take advantage of new biological understanding, novel therapeutic targets, multiple available and well-studied therapeutic strategies, and the necessary imaging techniques to measure outcomes. Their in-depth discussions cover the identification of new therapeutic targets and pathways, the investigation of transcriptional factors, master switch molecules, cell-based approaches, chemokines, a better understanding of the effects of aging, endothelial dysfunction, and hypercholesterolemia in response to angiogenic stimuli. Highlights include examination of drug delivery problems, outcomes measure, stem therapy, high-risk interventions, development pathways, and future possibilities. Authoritative and state-of-the-art, Angiogenesis and Direct Myocardial Revascularization provides all internists, cardiologists, vascular disease specialists, scientists, and industry with a highly effective scientific and clinical basis for helping patients with end-stage ischemic heart disease, peripheral vascular disease, and congestive heart failure.